Development and validation of a safety and health performance model for low cost housing - Ramli, Azuin (2014)
Sustainable building and construction practices in Malaysia are primarily aimed at improving the safety and health performance of buildings while minimizing its impact on resources and the natural environment. Thus, a comprehensive understanding of the factors that contribute to safety and health performance of our built environment is essential. The aim of this study is to develop a building safety and health performance (BSHP) model, focusing on the safety and health performance factors of low cost housing in Malaysia. These factors include the architecture, building services, external environment, operation and maintenance, and management approaches. The influence of these factors on perceived personal responsibility towards adopting a BSHP model for low-cost housing in Malaysia was also studied. This study was undertaken in two stages. Firstly, literature on existing safety and health practices related to low-cost housing and facilities were reviewed to identify factors that influence health and safety performance. Quantitative data were gathered to assess the suitability of the factors based on experts judgement and survey. Data obtained were statistically examined using the exploratory factor analysis (EFA) and the proposed model was identified. Secondly, quantitative data were gathered through a main survey involving 308 respondents to test the research model validity and the proposed hypothesis using the Partial Least Squares (PLS) tool. Results reveal that the five identified constructs have a direct positive effect on safety and health performance, as well as perceived personal responsibility. Furthermore, perceived personal responsibility (β = 0.563) towards safety and health performance has the highest beta value, followed by building services (β = 0.212), architecture (β = 0.155), operation and maintenance (β = 0.128), management approaches (β = 0.124), and external environment (β = 0.117). In testing the validity of models, results found BSHP model had a good model fit with R 2 of 0.342 and in line with experts validation results. The BSHP model can inform the public of the relative risks regarding the safety and health of low cost housing. It can also help building owners, developers, and government bodies to develop more informed and socially responsible decisions to improve building safety and health performance.